1999
DOI: 10.1093/jnci/91.11.954
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Human Papillomavirus DNA in Cytologically Normal Women and Subsequent Cervical Squamous Intraepithelial Lesions

Abstract: These findings are consistent with the hypothesis that HPV infection is the primary cause of cervical neoplasia. Furthermore, they support HPV vaccine research to prevent cervical cancer and efforts to develop HPV DNA diagnostic tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
128
2
8

Year Published

2000
2000
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(144 citation statements)
references
References 17 publications
6
128
2
8
Order By: Relevance
“…The relative risks found in other studies (Ho et al, 1998;Liaw et al, 1999), 10.0 and 12.7, respectively, are lower than the range studied here. One of the reasons may be that the other studies concern women aged around 20 years.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…The relative risks found in other studies (Ho et al, 1998;Liaw et al, 1999), 10.0 and 12.7, respectively, are lower than the range studied here. One of the reasons may be that the other studies concern women aged around 20 years.…”
Section: Discussioncontrasting
confidence: 79%
“…To estimate preclinical duration and sensitivity, longitudinal studies on the association between HPV infection and the development of neoplasias are necessary. Several large longitudinal screening studies have started, but no longterm results have been reported yet, although smaller longitudinal studies have been published (Rozendaal et al, 1996(Rozendaal et al, , 2000Ho et al, 1998;Liaw et al, 1999). These studies differ with respect to HPV test used, age range of women, study design, and cytological or histological endpoint, which complicates the comparison and interpretation of these results.…”
mentioning
confidence: 99%
“…As a molecular test, HPV DNA testing using HCII has an endpoint, expressed as a ratio of the test sample result compared with that of a known positive sample (1 pg/mL), that is independent of subjective morphologic interpretation. Because of the high correlation of HPV DNA results generated by HCII with PCR-based HPV testing (7) and the presence of SIL (5,(15)(16)(17), this approach (see Fig. 1 for flow chart) promises to provide accurate and reproducible information for quality assurance purposes in a highly efficient manner.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] Kaiser Permanente had not yet adopted the Bethesda System and still was using a modified dysplasia scale for cytologic interpretations. To cover the range of equivocal interpretations, we selected 200 conventional Papanicolaou (Pap) smears using stratified random sampling from computer records.…”
Section: Populationmentioning
confidence: 99%